Development of Kitchen Skills for Down Syndrome Students in Preparing Indonesian Gastronomy: Pengembangan Kitchen Skill Siswa Down Syndrome dalam Membuat Gastronomi Nusantara - Putri*, Dias Pratami; Insani, Hurry Mega; Bridha, Risya Ladiva; Meggy, Hendriano; Tresnawan, Iksan Kosasih; Risqiena, Naya Alia; Rafa, Maharani Maritza (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
An adaptive approach is required in the process of kitchen skills education for students with Down Syndrome to help them understand and master practical skills. The goal of this teaching activity is to increase the independence of Down Syndrome students through the visual learning method, especially at the service activity location, SLB Ngamprah Raya in West Bandung Regency. This method was chosen because students with Down Syndrome tend to have stronger visual comprehension, despite experiencing cognitive and physical limitations. This service activity involves cooking training using high-protein, gluten-free, and casein-free ingredients from Nusantara gastronomy, featuring a menu of Sate Lilit and Seaweed Jelly Ice. Through the visual approach, students can more easily understand the steps of cooking and improve their fine motor skills. The results of the activity show improvements in students' practical skills and confidence, as well as social benefits gained from participating in group activities. This indicates that visual learning is effective in supporting the development of life skills for students with special needs.